Factors influencing banking employee satisfaction in Saudi Arabia - Alqarawi, Alaa Brahim; AlSheail, Reef Mohammad (Archives of Business Research, 2019)
The main purpose of this research was to find out the factors that influenced employee’s satisfaction in order to enhance the employee’s functional commitment to employment and productivity. The study was based on primary data collected from banking industry in Saudi Arabia. A structured closed ended questionnaire was distributed among the employees of the Bank. The questionnaire used Likert Scale to from 1 to 5 for the responses of the employees. From literature factors impacting employee satisfaction were selected, these factors were (motivation - education - communication - trust - conflict - culture of the organization - human resources policies and practices). The analysis of the results of the questionnaire revealed that the incentives, education, organizational culture, human resource policies and practices have a positive impact on the job satisfaction of the Bank’s employees. While in relation to the factor of trust, conflict and communication, their impact was negative on the level of job satisfaction.